Digital Transformation and Servitization: The Keys to Unlocking Business Success in the Digital Age - Siskha Nur Khasanah; Jihan Rofifah; Ika Safitri; Mohamad Yusak Anshori (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2023)
Purpose – Emphasized that digital technology has a role in services across industries beyond manufacturing, including retail, banking, and the Internet of Things. Methodology – This study uses a combination of bibliometric analysis methodology and systematic literature review (SLR), to provide an inclusive view of the digital transformation that enable servitization in various industries. Findings – Organizations greatly profit when digital servitization plans are implemented successfully. First off, it increases revenue streams by expanding beyond just product sales as a source of money. Companies can tap into more income sources and attain better financial stability by providing complementary services and solutions. Second, by taking into account customers changing requirements and preferences, digital servitization raises customer happiness. Organizations may increase client loyalty, encourage repeat business, and build favorable brand perception by offering personalized and integrated services. Research limitations – The specific strategies, benefits, and disadvantages of digital servitization can vary depending on factors such as industry dynamics, company size, market conditions, and the successful execution of transformation initiatives. Organizations need to carefully assess their unique circumstances and tailor their digital servitization strategies accordingly to maximize the benefits and mitigate potential challenges. Practical implications – IoT, cloud computing, and data analytics are examples of digital technologies that businesses can adopt to optimize service delivery, boost operational effectiveness, and acquire insightful data on customer behavior. As a result, they are in a position to dominate their market and beat off rivals in the age of digital technology.